A brief aviation sustainable practices attitude scale: establishing validity and reliability. (2016) - Cremer, Ismael; Rice, Stephen; Michaels, Alexander; Oyman, Korhan
Previous research has focused on transportation sustainability in other arenas, and in aviation perception scales, but to date, no researcher that we know of has developed a valid and reliable scale to measure consumer attitudes of aviation sustainability practices. A pair of aviation sustainability practices attitude (ASPA) scales were created for the purpose of measuring consumer attitudes about their experiences with airport and airline sustainable activities. The direct purpose of these scales is to aid in measuring the level that consumers would rate various sustainable practices with regard to the environment. In this paper, we outline the methodology that was used. A previous sustainable attitude scale called the SUS-TAS developed by Choi and Sirakaya (2005) was used as a foundational basis for the current scales in this paper. A total of 669 participants were solicited to help test the final two scales for validity and reliability. A factor analysis using the principal components and varimax rotation loaded strongly on one factor in each scale, providing evidence for validity. Reliability was tested via Cronbach's alpha and Guttmann's split-half tests, indicating high consistency and reliability.